The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/msc.1051
|View full text |Cite
|
Sign up to set email alerts
|

Skin and Mucosa Care in Systemic Sclerosis – Patients' and Family Caregivers' Experiences and Expectations of a Specific Education Programme: A Qualitative Study

Abstract: Patients and family caregivers benefited from the individualized and SSc-specific education on skin and mucosa care. Future improvements to the programme should focus on imparting understandable information on SSc pathophysiology, dealing with disfigurement and seeking reliable disease information, as well as facilitating peer support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Diary methods of assessing the frequency and duration of SSc-RP assume a paradigm of episodic RP attacks and preclude adequate capture of a phenomenon familiar to SSc clinicians and previously described by Jill Belch as 'what is for many patients the worst feature of the disease continual digital ischaemia' [45]. The phrase 'my constant companion' was used by a patient to describe SSc-RP in one qualitative research study to allude to the persistent threat and/or presence of digital ischaemic symptoms experienced by many patients with SSc [8].…”
Section: Duration Of Rp Attacksmentioning
confidence: 99%
“…Diary methods of assessing the frequency and duration of SSc-RP assume a paradigm of episodic RP attacks and preclude adequate capture of a phenomenon familiar to SSc clinicians and previously described by Jill Belch as 'what is for many patients the worst feature of the disease continual digital ischaemia' [45]. The phrase 'my constant companion' was used by a patient to describe SSc-RP in one qualitative research study to allude to the persistent threat and/or presence of digital ischaemic symptoms experienced by many patients with SSc [8].…”
Section: Duration Of Rp Attacksmentioning
confidence: 99%
“…A recent systematic review identified 12 peer‐reviewed qualitative studies, including 380 patients, on the perspectives of patients with SSc , which found that patients face persistent uncertainties that undermine their self‐image, daily functioning, and identity. However, there are still knowledge gaps in the areas of information needs, attitudes to medications, self‐management, and support.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative methods can help evaluate patients’ experiences by identifying issues that would not arise within the prespecified boundaries of quantitative research . It has been recommended that complex interventions such as ERAS programmes should be assessed using both qualitative and quantitative methods , and this approach has previously been used successfully to explore patients’ experiences of various clinical programmes .…”
Section: Introductionmentioning
confidence: 99%